Design and Development of an Interactive Sex Education Book for Kindergarten Children - Paramytha Magdalena Sukarno Putri; Nadyalis Ta'mara Masajida; Chabibah Ilmiyah; Suci Puspita Ratih; Windi Chusniah Rachmawati (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Kindergarten is an ideal stage to introduce comprehensive sex education, as preschool children can learn holistically. However, reproductive health materials for kindergarten students remain limited and lack comprehensiveness. This study aims to develop educational media based on the International Technical Guidance on Sexuality Education to facilitate comprehensive sexuality education at the Laboratory Kindergarten, Universitas Negeri MalangMethod: The study utilized the Borg and Gall research model. Participants included four kindergarten teachers and 63 students, divided into two grades: grade A (ages 3–4) and grade B (ages 5–6) at the Laboratory Kindergarten, Universitas Negeri Malang.Result: The results show that the majority of teachers agree that the use of sentences in the book is in accordance with Indonesian language rules, pictures, and the purpose of the book. Furthermore, the feasibility test by 4 kindergarten teachers showed that the book is very feasible (percentage of feasibility > 82.25%). The lowest eligibility score was 83.3%, while the highest score was 100%. Based on the results of the calculation of the feasibility assessment, the book is very feasible to use as a health promotion media for early childhood.